Anaerobic digestion of pineapple peels and cores through biogas production / Nur Ainaa Mohd Fauzi ...[et al.] - Mohd Fauzi, Nur Ainaa; Mohd Shukri, Syarizad Sofia; Ismail, Muhamad Farizwan; Sukor, Mohd Zaki
Malaysia is one of the countries that contributed about 1 % production of pineapple. It produce great amount of waste per year. Pineapple wastes consist of peels, cores and crowns. Therefore, the environmental pollution occurs as the waste burnt in an open field. The illegal activities of disposing the waste are also happened as the landfills are limited. In order to reduce the environmental pollution, the pineapple waste which is rich in cellulose, hemicellulose and other carbohydrates is used in generation of biogas by anaerobic digestion. The pineapple waste is mixed in the 2 litres bioreactor with the inoculum which is wastewater. Toe initial pH value for the peels, cores, wastewater, water, and digester consist of pineapple with water and pineapple with wastewater were recorded. Toe ratio of pineapple peels to cores is 7:5 whereas the ratio of wastewater to pineapple peel and cores for 3 experiments are 4:2, 4:4 and 4:6 respectively. The biogas yield is observed and recorded for HRT 18 days. For comparison purpose, the constant sample was set up using water and pineapple peels and cores with the same ratio as experiment 1. The biogas yield is observed and recorded for 18 days. Lastly, the final pH values were recorded. The data recorded may vary the theory caused by the limitation faced and some recommendations were discuss